Leptin, ghrelin, and endocannabinoids: Potential therapeutic targets in anorexia nervosa - Støving, René Klinkby; Andries, Alin; Brixen, Kim; Flyvbjerg, Allan; Hørder, Kirsten; Frystyk, Jan (Journal of psychiatric research, 2009)
Anorexia nervosa (AN) has the highest mortality rate between psychiatric disorders, and evidence for managing it is still very limited. So far, pharmacological treatment has focused on a narrow range of drugs and only a few controlled studies have been performed. Furthermore, the studies have been of short duration and included a limited number of subjects, often heterogenic with regard to stage and acute nutritive status. Thus, novel approaches are urgently needed. Body weight homeostasis is tightly regulated throughout life. With the discovery of orexigenic and anorectic signals, an array of new molecular targets to control eating behavior has emerged. This review focuses on recent advances in three important signal systems: leptin, ghrelin, and endocannabinoids toward the identification of potential therapeutical breakthroughs in AN. Our review of the current literature shows that leptin may have therapeutic potentials in promoting restoration of menstrual cycles in weight restored patients, reducing motor restlessness in severely hyperactive patients, and preventing osteoporosis in chronic patients. Ghrelin and endocannabinoids exert orexigenic effects which may facilitate nutritional restoration. Leptin and endocannabinoids may exert antidepressive and anxiolytic effects. Finally, monitoring serum concentration of leptin may be useful in order to prevent refeeding syndrome.